A Model Based on Cocitation for Web Information Retrieval. (27th February 2014) - Xie, Yue; Huang, Ting-Zhu
Abstract : According to the relationship between authority and cocitation in HITS, we propose a new hyperlink weighting scheme to describe the strength of the relevancy between any two webpages. Then we combine hyperlink weight normalization and random surfing schemes as used in PageRank to justify the new model. In the new model based on cocitation (MBCC), the pages with stronger relevancy are assigned higher values, not just depending on the outlinks. This model combines both features of HITS and PageRank. Finally, we present the results of some numerical experiments, showing that the MBCC ranking agrees with the HITS ranking, especially in top 10. Meanwhile, MBCC keeps the superiority of PageRank, that is, existence and uniqueness of ranking vectors.